Criminal Sanctions for Coral Reef Destroyers Tomia Island Study, Wakatobi Regency - La Ode Muhammad Karim (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2022)
In general, damage to coral reefs in the Tomia Wakatobi area is caused by human activities, including fishing methods using explosives, disposal of plastic waste which causes pollution of the marine environment and other fishing methods that are not environmentally friendly which cause coral damage. This research uses empirical normative law research methods, which are legal research conducted by researching library materials or secondary data, normative legal research is also called doctrinal legal research. Peter Mahmud explained that normative legal research is a process to find a rule of law, legal principles, and legal doctrines in order to answer the legal issues faced. In this type of legal research, law is often conceptualized as what is written in legislation or regulations. The law is conceptualized as a rule or norm which is a benchmark for human behavior that is considered appropriate. The result of this study is that the regulation of sanctions for perpetrators of coral destruction is regulated in laws, including the Republic of Indonesia Law Number 31 of 2004 concerning Fisheries, which is specifically regulated in Article 84 paragraph (1) and Law no. 27 of 2007 concerning the management of coastal areas and small islands, in article 35 letters a, b, c, and d everyone is directly or indirectly prohibited from mining coral reefs that cause damage to coral reef ecosystems, taking coral reefs in conservation areas. The inhibiting factors in preventing coral destruction are the lack of public awareness and lack of supervision.